Dividend Policy of Manufacturing Companies Reviewed based on Managerial Ownership and Profit Growth - Hariany Idris; Helmia Nursyaqila Hamda (Universitas Negeri Makassar, 2023)
Thisl study aims to determine whether there is an effect of managerial ownership and profit growth on dividend policy in manufacturing companies. The variable of this research is managerial ownership as the independent variable (X1) which is measured by the percentage of the number of shares owned by management to the total number of shares owned by the company then multiplied by 100%. Profit growth as (X2) as an independent variable as measured using the ratio of current year's net profit (Yt) minus the previous net profit (Yt-1) to the previous year's net profit (Yt-1) then multiplied by 100%. And Dividend Policy asl the dependentl variable (Yl) as measuredl by thel Dividend Payout Ratio is the ratio that shows the results of the comparison between cash dividends per share and earnings per share then multiplied by 100%. The populationl in thisl study arel all manufacturing companiesl listed onl the Stockl Exchange. Indonesian Securities (IDXl) with al sample of three years froml 2019 to 2021 which was taken using a purposivel sampling ltechnique. Data collectionl was carried out usingl a documentation technique. Datal analysis wasl performed usingl descriptive statistical analysis, classic assumption test and hypothesis test with the help of IBM SPSS 25 software. The results of this study indicate that based on the results of simultaneous test calculations (F test), it can be seen that the calculated F value is 4,426 > F table 3,15 with a significant level of 0,016 < 0,05. So that managerial ownership and profit growth simultaneously or jointly have a significant effect on dividend policy. And the t test in the table shows the calculated t value for the managerial ownership variable of 1,889 and t table of 2,000. If the two are compared, then the t count is smaller than the t table (1,889 < 2,000). This shows that managerial ownership has no effect on significant dividend policy. As well as the profit growth variable, the value of t count is 2,553 > t table 2,000, which means that profit growth affects significant dividend policy. This is also supported by a significant value of 0,013< 0,05, which means that there is a significant influence between profit growth and dividend policy.